Low Motor Dexterity and Significant Behaviors Following Hospitalized Isolation in Children - Kaitlin Fraser; Miriam Kuhn; Rebecca Swanson; Don W. Coulter; Christopher Copeland; Jorge M. Zuniga (MDPI AG, 2023)
The main objective of this study was to describe the cortical patterns of brain activity during a gross dexterity task and develop a behavioral profile of children experiencing isolation. A cross-sectional assessment was conducted during one visit. Sample: Four pediatric patients who had undergone isolation within a hospital comprised the full data collection. During the collection, participants completed the Box and Blocks Test of gross manual dexterity while undergoing imaging of the motor cortex using functional near-infrared spectroscopy. Participants also completed a Behavioral Assessment System for Children, Third Edition (BASC-3) self-report, which was analyzed along with a parent report to quantify their emotional and social behaviors. All participants displayed lower gross dexterity levels than normative data. Furthermore, three out of the four participants displayed ipsilateral dominance of the motor cortex during the dexterity task. Three of the participants displayed behavioral measures reported within clinically significant or at-risk scores. Clinically significant behavioral scores coupled with lower than expected manual dexterity values and ipsilateral hemispheric dominance indicate that neuroplastic changes can occur in populations undergoing hospitalized isolation. While the impacts of the treatments and isolation in this case cannot be separated, further studies should be conducted to understand these impacts of isolation.